2020
DOI: 10.1002/andp.201900298
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Odd‐Frequency Pairing in Multiband Superconductors

Abstract: Recent progress in the understanding of multiband superconductivity and its relationship to odd‐frequency pairing are reviewed herein. The discussion begins by reviewing the emergence of odd‐frequency pairing in a simple two‐band model, providing a brief pedagogical overview of the formalism. Several examples of multiband superconducting systems are examined, in each case describing both the origin of the band degree of freedom and the nature of the odd‐frequency pairing. Throughout, it is attempted to convey … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 180 publications
(521 reference statements)
2
45
0
1
Order By: Relevance
“…3(c). Therefore, we conclude that band hybridization gives rise to pseudogaps at higher energies in the DOS of the SC SSH model, which is also similar to what occurs in certain two-band superconductors [46][47][48][49].…”
Section: B Winding Numbersupporting
confidence: 74%
See 1 more Smart Citation
“…3(c). Therefore, we conclude that band hybridization gives rise to pseudogaps at higher energies in the DOS of the SC SSH model, which is also similar to what occurs in certain two-band superconductors [46][47][48][49].…”
Section: B Winding Numbersupporting
confidence: 74%
“…Odd-ω pairing can also appear as a bulk effect in superconductors, without the need of interfaces. This occurs in systems with multiple degrees of freedom such as multiband superconductors [46][47][48][49], double quantum dots [50,51], and double nanowires [35,52], where the band, dot, or wire indices, respectively, allow for a more broadened family of Cooper pair symmetries where odd-ω correlations can then emerge without the need of interfaces as in junctions. In particular, in multiband superconductors it has been shown that odd-ω pairing can be correlated with observable signatures such as gaps in the density of states (DOS) at higher energies [47] and the Kerr effect [53,54].…”
Section: Introductionmentioning
confidence: 99%
“…The band inversion in Bi 2 Se 3 implies that the bulk conduction and valence bands are formed by two orbitals with different parity, originating from hybridized Se and Bi p z states. This orbital degree of freedom in the TI allows for the generation of odd-frequency pairing components, in addition to the even-frequency ones [47]. For a proximitycoupled TI to a singlet s-wave SC, the symmetry allowed odd-(even-) frequency components are odd (even) in the orbital index [38].…”
mentioning
confidence: 99%
“…where ζ = diag (1, 1, −1, −1), to find the scattering coefficients of Eqs. (19) and (22). Note that the effect of the interfacial RSOI enters through the boundary condition [38].…”
Section: Here T E(h)mentioning
confidence: 99%
“…This unusual pairing obeys some exotic symmetries, such as s-wave spin-triplet and p-wave spin-singlet symmetry [4]. It has mostly been found in hybrid structures like ferromagnet (FM)/superconductor (SC) [6][7][8][9][10][11], normal metal/SC [12][13][14][15], and multiband systems with inter-band hybridization [16][17][18][19].…”
Section: Introductionmentioning
confidence: 98%